Visible-Light-Promoted Click [3+2] Cycloaddition of Aziridine with Alkyne: An Efficient Synthesis of Dihydropyrrolidine - Kapoor, Ritu; Chawla, Ruchi; Verma, Ankit; Keshari, Twinkle; Siddiqui, I. R. (Synlett, 2023)
A photocatalytic [3+2] cycloaddition of aziridines with activated alkynes is reported under visible-light irradiation in the presence of ruthenium catalyst. This chemical transformation provides polysubstituted pyrrolidines in good yields based on the click chemistry philosophy. The reaction successfully represents a primary trial of cyclocarboamination through photocascade catalysis combining energy transfer and redox neutral reactions.
Keywords: aziridine; alkyne; dihydropyrrolidine; visible light; click chemistry; photoredox catalysis